NUMERICAL ANALYSIS OF THE PARAFFIN MELTING PROCESS IN A SQUARE CAVITY WITH INCREASE GRADUALLY OF HOT WALL TEMPERATURE - Agus Dwi Korawan (Universitas Mercu Buana, 2020)
Paraffin as a heat storage material has many advantages but also has drawbacks, namely low thermal conductivity so that the melting time becomes long. Efforts have been made to accelerate the melting time, including by increasing a surface area of the hot wall, or also by changing the geometry. In this study was carried out by changing the temperature of the hot wall from uniform to increase gradually, uniform hot wall temperature was 330 K, increased gradually hot wall temperature was 324 K, 327 K, 330 K, 333 K, dan 336 K. Paraffin used has specifications according to reference. They have performed numerically used ANSYS software. They are using three models, namely modelA, model-B, and model-C. The study aimed to obtain liquid-solid interface contours, changes in temperature at measurement points, and changes in the liquid fraction. The results of model validation show similarities to previous studies. The results show that the melting time in the model-A is the fastest, followed by model-B and model-C.